Incidence and extent of TDP-43 accumulation in aging human brain - Uchino, Akiko (Acta Neuropathol Commun, 2015)
INTRODUCTION: The transactivation response element DNA-binding protein 43 kDa (TDP-43) is a major component of the ubiquitin-positive and tau-negative inclusions in frontotemporal lobar degeneration and sporadic amyotrophic lateral sclerosis (ALS). TDP-43 may accumulate in cases of Alzheimer’s disease (AD), Lewy body disease (LBD), and argyrophilic grain disease (AGD). However, few studies have focused on the incidence and extent of TDP-43 deposition in aging. RESULTS: We analyzed 286 consecutive autopsy brains neuropathologically. Of these, 136 brains with pathologically minimal senile changes were designated as control elderly brains (78.5 ± 9.7 y). For comparison, we selected 29 AD, 11 LBD, and 11 AGD patients from this series of autopsy brains. Sections of the hippocampus, amygdala, medulla oblongata, and lumbar spinal cord were immunostained with anti-phosphorylated TDP-43 antibody (PSer409/410). TDP-43 immunoreactive structures were classified into four types: dystrophic neurites (DNs), neuronal or glial cytoplasmic inclusions, and intranuclear inclusions. TDP-43 immunoreactive structures were observed in 55/136 control elderly (40.0 %), 21/29 AD (72.4 %), 8/11 LBD (72.7 %), and 6/11 AGD (54.5 %) brains. TDP-43 immunoreactive structures in control elderly brains were mostly DNs. These DNs were predominantly present in the uncus of the anterior hippocampus over age 65. The frequency of cases with DNs in the amygdala of control elderly brains was less than that of AD, LBD, and AGD brains. The mean age at death was significantly higher in cases with TDP-43 immunoreactive structures than cases without them. CONCLUSIONS: In conclusion, TDP-43 immunoreactive DNs may develop as a consequence of aging processes in the human brain. In particular, the uncus of the anterior hippocampus is an area highly susceptible to TDP-43 accumulation over age 65.